ANALYZING THE IMPACT OF PROMOTIONAL MIX ON CCTV PURCHASE DECISIONS AT PT. MITRA MANAKARRA PROTEKSI IN MAMUJU DISTRICT - Dirgahayu Dirgahayu; Ramli Ramli; Iwan Adinugroho (Jurnal Ekonomi, 2023)
This research examined the influence of the promotional mix, including Advertising, Personal Selling, Publicity, and Sales Promotion, on the purchase decisions of CCTV systems at PT. Mitra Manakarra Proteksi in Mamuju District. The study employed quantitative and qualitative data collection methods, with a sample of 50 customers who had purchased CCTV products. The analysis revealed significant positive effects of all four promotional elements on CCTV purchase decisions. Additionally, the coefficient of determination (R2) indicated that 73.00% of the variance in purchase decisions could be explained by these promotional strategies. However, approximately 27.00% of the variance remained unexplained, suggesting the presence of other influencing factors. These findings emphasize the importance of effective promotional strategies in driving customer purchase decisions in the CCTV industry.